Process of Social Transformation among women in India - Sara, Nazhath (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
A woman is a human being she has a soul similar to that of a man. A woman defined as the feminine component of the human species who, apart from serving as a vehicle for nurturing human life also equally contribute in social, economic and political development in society.The concept of social transformation have a similar definition as social change, many authors have used both terms interchangeably.Social change refers to fundamental changes in the social structure, patterns of culture and social behavior. Changemeans variations or a difference in anything observed over some period of time. Social change is very complex. Since society is a process not product. If it had been product then there would not have been changes. Processes are ongoing change therefore they bound to change. Society is changeful and dynamic. We can say that change is a law of society unchanging society is a myth. Hence, social change is important for society as well as women. In this paper attempt has been made to analyze social change taking place in India especially among Indian women.